Characterization of Simian-Human Immunodeficiency Virus Envelope Glycoprotein Epitopes Recognized by Neutralizing Antibodies from Infected Monkeys - Etemad-Moghadam, Bijan (American Society for Microbiology, 1998)
We characterized human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein epitopes recognized by neutralizing antibodies from monkeys recently infected by molecularly cloned simian-human immunodeficiency virus (SHIV) variants. The early neutralizing antibody response in each infected animal was directed mainly against a single epitope. This primary neutralizing epitope, however, differed among individual monkeys infected by identical viruses. Two such neutralization epitopes were determined by sequences in the V2 and V3 loops of the gp120 envelope glycoprotein, while a third neutralization epitope, apparently discontinuous, was determined by both V2 and V3 sequences. These results indicate that the early neutralizing antibody response in SHIV-infected monkeys is monospecific and directed against epitopes composed of the gp120 V2 and V3 variable loops.